Teaching extension through intergenerational dialogues in the Humanities classrooms: memory and literature 45 years after the coup in Chile - Gutiérrez Rojas, Marisol (2020)
The article gathers the experience of a social action project carried out on the occasion of the 45th anniversary of the coup d'etat in Chile, at the Escuela de Estudios Generales of the University of Costa Rica. Its objective was to generate spaces for intergenerational dialogue in order to work on memory from literature. In that sense, a greater involvement of society was sought in order to raise awareness in relation to human rights, a fundamental aspect of general and humanistic education.